Stationary Navier–Stokes equations with non-homogeneous boundary condition in a system of two connected layers - Kaulakytė, Kristina (Lietuvos matematikos rinkinys, 2012)
In this paper the stationary Navier–Stokes system with non-homogeneous boundary condition is studied in domain which consists of two connected layers. The extension of the boundary value, which reduces the non-homogeneous boundary problem to the homogeneous one, is constructed in this paper.